Engineering of Biodegradable and Excretable Inflammation‐Resolving Materials (Adv. Funct. Mater. 41/2022). (10th October 2022) - Wu, Peng; Gao, Mingjie; Zhang, Chunfan; Li, Chenwen; Li, Gang; Yan, Xinhao; Lai, Xiaodan; Zhang, Yang; Zhang, Jianxiang
Abstract : Bioactive Materials In article number 2205528, Jianxiang Zhang and co‐workers report a series of inflammation‐resolving biomaterials engineered by integrating different functional modules into a hydrolysable scaffold, which can assemble into anti‐inflammatory micelles capable of eliminating reactive oxygen species, releasing bioactive molecules, and simultaneously hydrolyzing into water‐soluble and excretable compounds, thereby efficaciously alleviating acute kidney injury and acute liver failure.